[OP.4B.01] EFFECTS OF DAPAGLIFLOZIN ON EARLY ALTERATIONS OF THE MICRO- AND MACROCIRCULATION IN PATIENTS WITH TYPE-2 DIABETES. (September 2017) - Ott, C.; Kistner, I.; Jumar, A.; Friedrich, S.; Bramlage, P.; Schmieder, R.E.
Abstract : Objective: Diabetes mellitus, primarily a metabolic disorder, must be considered also as a vascular disease. Early vascular changes are characterized by hyperperfusion (e.g. eye), vascular remodeling of small arteries and increased pulse wave reflection leading to increased (central) aortic pressure. We investigated the effects of the SGLT-2 inhibitor dapagliflozin on parameters of early micro- and macrovascular changes in patients with type-2 diabetes. Design and method: In this prospective, double-blind, placebo-controlled, cross-over trial 59 patients (61 ± 7.6 years) with type-2 diabetes were randomly assigned to dapagliflozin 10 mg and placebo for 6 weeks. Retinal microvascular structure (wall-to-lumen ratio [WLR]) and retinal capillary flow [RCF]) were non-invasively assessed by scanning laser Doppler flowmetry. In addition, macrovascular parameters (central pulse pressure) were assessed by pulse wave analysis in addition to 24-h ambulatory blood pressure (ABP). Results: Treatment with dapagliflozin for 6 weeks improved diabetic control (HbA1c, fasting and postprandial blood glucose, all p < 0.001) compared to placebo. Compared to placebo treatment with dapagliflozin reduced numerically but not significantly both microvascular parameters (RCF and WLR). When compared to baseline, treatment with dapagliflozin reduced RCF (308 ± 78 vs. 324 ± 84 AU, p = 0.028), indicative of a normalization of retinal hyperperfusion, and prevented vascular remodelling of retinal, which occurred in the placebo group (WLR: 0.356 ± 0.1 vs. 0.391 ± 0.1, p = 0.034). Moreover, compared to placebo, treatment of dapagliflozin reduced systolic and diastolic 24-h ABP (126 ± 11/75 ± 8 vs. 129 ± 12/77 ± 7 mmHg, p = 0.021/0.027), and central pulse pressure (40.9 ± 11 vs. 43.9 ± 12 mmHg, p = 0.05). Conclusions: Overall, our data indicate that treatment with the SGLT-2 inhibitor dapagliflozin exerts beneficial effects on vascular parameters of the micro- and macrocirculation, suggesting an improvement of cardiovascular prognosis.